Mining scraper conveyor sprocket replacement and repair evaluation method - LIU Huifeng; GAO Zhong; ZHAO Lijia (Jixie chuandong)
ObjectiveThe excessive wear of the scraper conveyor sprocket and the over-life working condition will lead to the occurrence of the stuck chain, broken chain and other faults, which will adversely affect the normal operation of the conveyor equipment. In order to guide users to replace the sprocket that is not suitable for further use and reduce the incidence of equipment failure, a mining scraper conveyor sprocket replacement and repair evaluation method was proposed.MethodsBased on the Archard wear theory, firstly, the hardness characteristics of the quench hardness layer of the sprocket were studied, and then the dynamic simulation analysis on the meshing transmission process of the ring chain drive system under different wear degree of the sprocket was carried out. The dynamic characteristics of the scraper conveyor were tested to verify the accuracy of the simulation analysis.ResultsThe test results show that when the wear depth of the sprocket chain socket reaches the maximum quenching hardness layer depth, the performance of the sprocket has decreased significantly, and the sprocket should be replaced. When the speed fluctuation, the contact force and the tension increase abnormally in the ring chain drive system, the sprocket should also be replaced in time to ensure the stable operation of the equipment. The proposed method provides a basis for the maintenance and replacement of the scraper conveyor sprocket.